Memahami Sistem Pengetahuan Budaya Masyarakat Pegunungan Tengah, Jayawijaya, Papua dalam Konteks Kebencanaan - Veronika Leny (Antropologi Indonesia, 2013)
Jayawijaya suffers from hazards stemming from natural and human-made-disaster (anthropogenic). Dani tribe resided in Jayawijaya is known to dwell on profound influence of culture and nature allowing genuine local knowledge in managing disaster risks to breed. This study aims to understand the cultural knowledge systems of Dani tribe relating to disaster and its practices. This study is developed from desk studies and interviews with stakeholders. Dani tribe has known the concept of human-and-human and human-and-nature unison. They define this concept as transcendence relationship. Harmonious relationship between human and nature is believed would influence livelihood and in contrast would engender various forms of disaster. As part of securing their well-being, Dani tribe formulates norms which is manifested in various practices such as: environmental protection which includes rules and sanctions; the establishment of war command post and tribal structure consisted of commander of war and the head of fertility who govern war threads and initiate peace; as well as ritual performances. Living in harmony with nature allows Dani tribe to interpret these signs of nature as an early warning of disaster. Hopefully, the results of this study would be beneficial to local governments, customary institutions, faith-based institutions, and stakeholders in an effort to build community resilience.Keywords: disaster risk reduction, social and cultural systems, local knowledge, Dani, Jayawijaya, community resilience